Turning green: the impact of changing to more eco-friendly respiratory healthcare – a carbon and cost analysis of Dutch prescription data - Evelyn A Brakema; johan Kooistra; Niels Chavannes; Paul Hagedoorn; Pieter ten Have; Peter van Hal; Iris Wichers; Pauline de Heer; Hans C Ossebaard (BMJ Open)
Objectives Dry powder inhalers (DPIs) and soft mist inhalers have a substantially lower global warming potential than pressurised metered-dose inhalers (pMDIs). To help mitigate climate change, we assessed the potential emission reduction in CO2 equivalents when replacing pMDIs by non-propellant inhalers (NPIs) in Dutch respiratory healthcare and estimated the associated cost.Design We performed a descriptive analysis of prescription data from two national databases of two independent governmental bodies. First, we calculated the number of patients with chronic obstructive pulmonary disease (COPD) and asthma that were using inhalation medication (2020). Second, we calculated the number and total of daily defined doses of pMDIs and NPIs including DPIs and soft mist inhalers, as well as the number of dispensed spacers per patient (2020). Third, we estimated the potential emission reduction in CO2 equivalents if 70% of patients would switch from using pMDIs to using NPIs. Fourth, we performed a budget impact analysis.Setting Dutch respiratory healthcare.Primary and secondary outcome measures The carbon footprint of current inhalation medication and the environmental and financial impact of replacing pMDIs with NPIs.Results In 2020, 1.4 million patients used inhalers for COPD or asthma treatment. A total of 364 million defined daily doses from inhalers were dispensed of which 49.6% were dispensed through pMDIs. We estimated that this could be reduced by 70% which would lead to an annual reduction in greenhouse gas emission of 63 million kg.CO2 equivalents saving at best EUR 49.1 million per year.Conclusions In the Netherlands, substitution of pMDIs to NPIs for eligible patients is theoretically safe and in accordance with medical guidelines, while reducing greenhouse gas emission by 63 million kg.CO2 equivalents on average and saving at best EUR 49.1 million per year. This study confirms the potential climate and economic benefit of delivering a more eco-friendly respiratory care.